2018
DOI: 10.1159/000492389
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Neutrophil/Lymphocyte Ratio in Patients with Non-Human Papilloma Virus-Related Oropharyngeal Cancer: A Retrospective Cohort Study

Abstract: Purpose: To investigate the effects of the pretreatment neutrophil-to-lymphocyte ratio (N/L) on non-human papilloma virus (HPV)-related oropharyngeal cancer. Materials and Methods: N/L was calculated by dividing the neutrophil count by the lymphocyte count. Survival outcomes were estimated using the Kaplan-Meier method and compared by the log-rank test. Univariate and multivariate analyses were performed to evaluate the prognostic impact of N/L and other clinical factors on survival outcomes. High/low N/L grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…In another one from Gorphe et al, in patients with p16-positive OPC, a NLR > 5 was correlated with worse OS and resulted to be an independent prognostic factor together with Hb level (Gorphe et al, 2018). Also in a recent published study, in non-HPV-related oropharyngeal patients, NLR maintained an important independent role in cancer progression and had an important prognostic value (De Felice et al, 2019). In our analysis, no differences were observed in terms of NLR in HPV-positive and HPV-negative F I G U R E 1 Univariate analysis of progression-free survival and overall survival for patients with neutrophil-tolymphocyte ratio (NLR) <3 (filled lines) and ≥3 (dashed lines) F I G U R E 2 Neutrophil-to-lymphocyte ratio (NLR) pretreatment and post-treatment in non-complete responders versus complete responders after chemoradiotherapy (CRT) [Colour figure can be viewed at wileyonlinelibrary.com] patients, postulating that NLR maintains its independent prognostic role.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In another one from Gorphe et al, in patients with p16-positive OPC, a NLR > 5 was correlated with worse OS and resulted to be an independent prognostic factor together with Hb level (Gorphe et al, 2018). Also in a recent published study, in non-HPV-related oropharyngeal patients, NLR maintained an important independent role in cancer progression and had an important prognostic value (De Felice et al, 2019). In our analysis, no differences were observed in terms of NLR in HPV-positive and HPV-negative F I G U R E 1 Univariate analysis of progression-free survival and overall survival for patients with neutrophil-tolymphocyte ratio (NLR) <3 (filled lines) and ≥3 (dashed lines) F I G U R E 2 Neutrophil-to-lymphocyte ratio (NLR) pretreatment and post-treatment in non-complete responders versus complete responders after chemoradiotherapy (CRT) [Colour figure can be viewed at wileyonlinelibrary.com] patients, postulating that NLR maintains its independent prognostic role.…”
Section: Discussionmentioning
confidence: 84%
“…Preliminary results also showed that NLR maintained its prognostic value both in HPV-positive and non-HPV-related tumours. Moreover, two recent reports (De Felice et al, 2019;Gorphe et al, 2018) confirmed that NRL ratio maintains its prognostic value according to both TNM 8th ed. and the previous edition.…”
Section: Introductionmentioning
confidence: 81%
“…The role of inflammation has been well investigated in cancer biology (De Felice et al., 2019), and the circulating leucocyte count appears to be elevated as well as functionally different in cancer patients versus healthy population ([Fernandes et al., 2007; Trellakis et al., 2011). The ratios between neutrophil and other leucocytes can reflect the status of systematic inflammation, and these ratios have been demonstrated as a prognostic and predictive factor of disease activity in various cancers, and accumulating evidences have suggested that pre‐treatment ratios between neutrophil and the other leucocytes such as monocytes and lymphocytes are related to the prognosis of a variety of some cancers (Huang et al., 2015; Chun et al., 2017; De Felice et al., 2019; Fernandes et al., 2007; Trellakis et al., 2011). Tumour‐infiltrating neutrophils can release cytokines to promote angiogenesis, which leads to tumour growth and metastasis (Huang et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The most important difference of our study from the ones in the literature is that patients who have just been met to the virus and have not yet developed malignancy were included in our study, while the patients who have already developed malignancy had been analysed in other studies in the literature. The reason for the difference in the results of some studies in the literature may be that patients with malignancies of different stages and sizes were included in those studies (Huang et al., 2015; Chun et al., 2017; De Felice et al., 2019; Li et al., ,2016, 2017; Wu et al., 2017; Farzaneh et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation